Microbe-Mediated Thermotolerance in Plants and Pertinent Mechanisms- A Meta-Analysis and Review - Dastogeer, Khondoker M. G.; Zahan, Mst. I.; Rhaman, Mohammad S.; Sarker, Mohammad S. A.; Chakraborty, Anindita (Frontiers in Microbiology, 2022)
Microbial symbionts can mediate plant stress responses by enhancing thermal tolerance, but less attention has been paid to measuring these effects across plant-microbe studies. We performed a meta-analysis of published studies as well as discussed with relevant literature to determine how the symbionts influence plant responses under non-stressed vs. thermal-stressed conditions. As compared to non-inoculated plants, inoculated plants had significantly higher biomass and photosynthesis under heat stress conditions. A significantly decreased accumulation of malondialdehyde (MDA) and hydrogen peroxide (H2O2) indicated a lower oxidation level in the colonized plants, which was also correlated with the higher activity of catalase, peroxidase, glutathione reductase enzymes due to microbial colonization under heat stress. However, the activity of superoxide dismutase, ascorbate oxidase, ascorbate peroxidase, and proline were variable. Our meta-analysis revealed that microbial colonization influenced plant growth and physiology, but their effects were more noticeable when their host plants were exposed to high-temperature stress than when they grew under ambient temperature conditions. We discussed the mechanisms of microbial conferred plant thermotolerance, including at the molecular level based on the available literature. Further, we highlighted and proposed future directions towards exploring the effects of symbionts on the heat tolerances of plants for their implications in sustainable agricultural production.